2019
DOI: 10.1007/s12155-019-09996-3
|View full text |Cite
|
Sign up to set email alerts
|

Can reduced tillage sustain sugarcane yield and soil carbon if straw is removed?

Abstract: Straw removal for bioelectricity, cellulosic ethanol, or other bio-products has become a common practice in Brazilian sugarcane areas, but long-term effects on soil organic carbon (SOC) and yield are unknown. Our objective was to quantify tillage intensity and removal levels on SOC stocks and sugarcane yield on contrasting edaphoclimatic conditions in Brazil. Conventional tillage-CT and reduced tillage-RT coupled with three straw removal levels (none-NR; moderate-MR; total-TR) were combined to create six treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 57 publications
4
39
0
8
Order By: Relevance
“…The higher sugarcane yield responses to straw removal in fine-textured soils (clayey) are associated with higher water storage capacity, which results in a high capacity to respond to management practices, especially when the water is the main limiting factor for sugarcane growth. The maintenance of straw also increases soil carbon stocks [12,43] and consequently tends to improve water-use efficiency in sugarcane fields [44]. Additionally, the benefits of straw mulching go beyond of soil water, since it contributes for soil organic matter formation, which plays an important role in improving cation exchange capacity in highly weathered tropical soils [45].…”
Section: Soil Texture Affecting Sugarcane Yield Response To Straw Remmentioning
confidence: 99%
“…The higher sugarcane yield responses to straw removal in fine-textured soils (clayey) are associated with higher water storage capacity, which results in a high capacity to respond to management practices, especially when the water is the main limiting factor for sugarcane growth. The maintenance of straw also increases soil carbon stocks [12,43] and consequently tends to improve water-use efficiency in sugarcane fields [44]. Additionally, the benefits of straw mulching go beyond of soil water, since it contributes for soil organic matter formation, which plays an important role in improving cation exchange capacity in highly weathered tropical soils [45].…”
Section: Soil Texture Affecting Sugarcane Yield Response To Straw Remmentioning
confidence: 99%
“…However, it is important to mention that this study evaluated only the implications of straw removal on N O emissions and did not account for changes in SOC stocks. Several studies have indicated that straw is an important source of C to the soil [25,[55][56][57] and the indiscriminate removal of this crop residue depletes SOC stocks in sugarcane fields [58,59]. Aligned with these results, previous studies on GHG balance of sugarcane ethanol have shown that SOC stock change is an important component of the overall GHG balance in sugarcane fields [5,60,61].…”
Section: Implications Of Straw Removal For Soil Ch 4 Emissionsmentioning
confidence: 82%
“…No removal straw in sugarcane increased the means of TCH and TPH at the lowest nitrogen rates (Figures 2E and 2G). The amount of trash used in this experiment was in the mean lower than in commercial Despite several studies show that C inputs annually added to soil through sugarcane straw resulted in soil C and N stocks accretion (Cerri et al, 2011;Cherubin et al, 2018;Oliveira et al, 2017;Tenelli et al, 2019), the linear responses of sugarcane to N rates show that, in order to ensure high sugarcane yield harvested without fire dispatch and intercropping Brachiaria grass, at least in the first years, need to apply high N rates. The low SOM content (Table 1), Brachiaria grasses intercropping in sugarcane fields, reduced soil tillage (direct furrowing), the high N demand of sugarcane, N losses by leaching into the sandy soils and decomposition of plant material with a high C/N ration (Brachiaria and trash), explain these results (Luz et al, 2017;Vitti et al, 2010).…”
Section: H) G)mentioning
confidence: 86%
“…In view thereof, conservation-focused agricultural practices have to be implemented to avoid soil and water losses by erosion, avoid soil drying and high temperatures that affect the microbial biomass activity, maintain and/ or increase the nutrient use efficiency, nutrient cycling, carbon input in the soil, and increasing the soil production potential in the long term. In sugarcane fields, mainly where mechanical management is used, the no-tillage (direct planting) system can be implemented, with planting under the trash of a previous unburned ratoon crop and stubble of crops or green manure residues (Bolonhezi;Gonçalves, 2015;Canellas et al, 2007;Cherubin et al, 2019;Santos Júnior et al, 2015;Signor et al, 2016;Tavares et al, 2010;Oliveira et al, 2017;Tenelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation